An Overview of International Relations in the Constitution of Pakistan - Fahd Rauf Bhatti,; Imdad Ullah,; Naveed Ahmad,; Muhammad Waris,; Fanoos Safdar Shah,; Inayatullah Khan, (Al-Qanṭara, 2023)
Foreign policy is a symbol of integrity of the country without which no country can stand alone on the World map. This was the basic point which was realized by the founder of Pakistan even before the establishment of Pakistan. Quaid-e-Azam had said in 1946 that naturally no nation can sustain its existence alone, rather there will be unity and agreement between nations and it will be with nations that have common interests. The integrity of Pakistan lies more in ideological security than geographical security. When we look at the basic principle of Pakistan's foreign policy in the light of the Quaid-e-Azam's edicts this is what is evident from it that he had initially described Pakistan's foreign policy keeping these conditions in mind that Islam is a religion of peace, brotherhood, love and freedom. The foreign policy of this country will be the bearer of letters. We believe in the principle of co-existence with integrity. Pakistan's foreign policy continued to be based on the strategy of survival in its evolutionary perianal. Quaid-e-Azam expressed that Pakistan's foreign policy will be based on friendship with other nations.